A-3b=9
a=b-3
b-3-3b=9
-2b-3=9
-2b=12
2b=-12
b=-6
a=-6-3
a=-9
Solution: (-9,-6)
----
Check:
-9=-6-3
-9=-9
TRUE
Eybrbdbfbrjhebrbfjhfhrhrbrvhfhfjf
I believe the answer is 1/531441
Add the following polynomials:
All polynomials are already ordered according to their degree (exponent), and therefore you can just add straight down in columns.
For x3: 2 + 1 - 3 = 0
For x2: -4 + 6 + 2 = 4
For x: 6 - 8 -4 = -6
Constants: -3 + 12 - 7 = 2
The answer is:
4x^2 - 6x + 2
Answer:
(1, 8.5 ) and ( - 17, 80.5 )
Step-by-step explanation:
Given the 2 equations
y =
x² + 4x + 4 → (1)
y = - 4x + 12
→ (2)
Substitute (1) into (2), that is
x² + 4x + 4 = - 4x + 12
( multiply through by 2 to clear the fractions )
x² + 8x + 8 = - 8x + 25 ( add 8x to both sides )
x² + 16x + 8 = 25 ( subtract 25 from both sides )
x² + 16x - 17 = 0 ← in standard form
(x + 17)(x - 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 17 = 0 ⇒ x = - 17
x - 1 = 0 ⇒ x = 1
Substitute these values into either of the 2 equations and evaluate for y
Substituting into (2 )
x = 1 : y = - 4(1) + 12.5 = - 4 + 12.5 = 8.5 ⇒ (1, 8.5 )
x = - 17 : y = - 4(- 17) + 12.5 = 68 + 12.5 = 80.5 ⇒ (- 17, 80.5 )